PENGELOLAAN KEUANGAN DESA BERBASIS AKUNTABILITAS UNTUK PEMBERDAYAAN EKONOMI LOKAL - Riduan Siagian; Parlaban Karo-Karo; Banpen Syahputra (Nusantara Hasana Journal, 2025)
This program aims to strengthen village financial management based on accountability to ensure that village expenditures are more targeted and have a tangible impact on local economic empowerment (village MSMEs, Village-Owned Enterprises/BUMDes, farmer/fisher groups, and productive households). The activities are carried out through mapping the processes and risks of financial management (planning–budgeting–implementation–administration–reporting), developing Standard Operating Procedures (SOPs) and accountability checklists, enhancing public information transparency, and providing assistance in designing measurable local economic program packages (output–outcome indicators). The main outputs include SOPs, role matrices, document control instruments, realization dashboards and local economic indicators, as well as an action plan for village economic empowerment.